(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Postoperative nausea and vomiting (PONV) has long been a common headache that accompanies caesarean section with spinal anaesthesia and leads to patient agitation, impaired recovery, and risk of comorbidities. The present study is done to establish the effectiveness of ondansetron, dexamethasone, and the combination in prevention of PONV in caesarean section patients of Diphu Medical College and Hospital, Assam. Method: A total of 159 pregnant women, aged between 25 and 35 years, were randomly assigned into three groups (Group A, 4 mg dose; Group B, 8 mg dose; and Group C, Combination dose). The study employed a randomized, double-blind design with intraoperative and postoperative monitoring of nausea, vomiting, and key parameters. Result: Results showed that the combination therapy (Group C) significantly reduced the incidence of both intraoperative (3.8%) and postoperative nausea (3.8%) compared to ondansetron alone (15.1% and 13.2%) and dexamethasone alone (41.5% for both). Notably, postoperative vomiting was absent in the combination group, whereas it occurred in 17% and 26.4% of patients in Groups A and B, respectively. Statistical analysis confirmed the significance of these findings (p < 0.05). Additionally, combination therapy demonstrated a lower frequency of side effects such as headache, dizziness, and rashes compared to monotherapy. Conclusion:Based on the results, the combined ondansetron and dexamethasone approach exhibited stronger antiemetic activity over monotherapy, decreased random drug related adverse events and results in better PONV prophylaxis in caesarean sections under spinal anaesthesia.